AGREEMENT ON THE JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) BETWEEN IRAN AND THE UNITED STATES - Mohamad Amine El Khalfi (UNISSULA, 2020)
Joint Comprehensive Plan of Action (JCPOA) is the result of diplomatic negotiations reached by the United States, Britain, France, Russia, China, Germany and Iran in 2015 regarding the Iran Nuclear Agreement. The emergence of this agreement was due to Iran's actions abusing its nuclear development to serve as a weapon of mass destruction in 2011. In response to this, Western countries imposed economic sanctions on Iran in the hope of weakening Iran's position so that it does not have the ability to continue its nuclear weapons program. In fact, these sanctions succeeded in weakening the Iranian economy but were not politically effective enough because the Iranian government remained strong, this led to Iran being still involved in various conflicts in the region and still insisting on developing its uranium enrichment. Iran's tough stance made Western countries choose to bring Iran into the negotiations by making offers that could attract Iran's attention. During the Obama administration, the United States succeeded in bringing Iran into the negotiations. An achievement when the United States together with Britain, France, Russia, China, and Germany succeeded in getting Iran to agree to stop developing its nuclear weapons in exchange for the lifting of sanctions from the West. However, when the Donald Trump administration tensions began to re-emerge with the assassination of one of Iran's war generals that took place in 2020. The United States succeeded in bringing Iran into the talks. An achievement when the United States together with Britain, France, Russia, China, and Germany succeeded in getting Iran to agree to stop developing its nuclear weapons in exchange for the lifting of sanctions from the West. However, when the Donald Trump administration tensions began to re-emerge with the assassination of one of Iran's war generals that took place in 2020. The United States succeeded in bringing Iran into the negotiations. An achievement when the United States together with Britain, France, Russia, China, and Germany succeeded in getting Iran to agree to stop developing its nuclear weapons in exchange for the lifting of sanctions from the West. However, when the Donald Trump administration tensions began to re-emerge with the assassination of one of Iran's war generals that took place in 2020.